Analisis Multimodal Representasi Ibu pada Feed Instagram @jokowi: Ibu Yang Berdaya (?) - Samuel Rihi Hadi Utomo (Calathu: Jurnal Ilmu Komunikasi, 2023)
This research explores how the representation of mothers is articulated in the upload "Happy Mother's Day" on the Instagram feed account @jokowi (22 December 2022). The qualitative research method and the multimodal analysis perspective of Kress and van Leeuwen (1996/2006) helped the writer to find out more deeply about the meaning that is built from the representation of the mother in the uploaded Instagram feed. The multimodal analysis in this study shows that IG's feed work is a form of popular culture with various modes in it to articulate meaning. This Instagram feed upload is a space for representing mothers who are idealized by culture and the media, patriarchal culture plays an important role in prescribing representations of mothers. The pink color with the meaning attached to it shows the representation of mother like two sides of a coin, one side gives the meaning of tenderness, affection, sympathy and understanding, but on the other hand, gives the meaning of being immature and inexperienced. Or in other words, position it as an object and passive. The media prescribes representations of mothers who have ideal and fashionable bodies, eye-catching from the clothes they wear. There are various representations of mothers who have not yet entered the Instagram feed representation space, so representations of mothers are not singular, but plural, they become visible and heard because they play an important role in the nation's journey, empowered in many ways for a more advanced Indonesia. Keywords: multimodal, representation, mother, Instagram, Jokowi